ReUnidos: Farmworker Skin Cancer Health Navigation Program. Issue 28 (1st October 2022) - Savage, David James; Tushla, Lisa A.; Guenin, Katie; Gross, Isabel; Kanakarajavelu, Nina; Young, Rebecca; Merino-Gonzalez, Deysi; Stamm, Nannette; Swetter, Susan M.; Boiko, Susan; Mofid, Mona Z; Guild, Samantha; et al.
Abstract : 113 Background: Farmworkers are at increased risk for skin cancer because of occupational exposure to sun and pesticides. In 2017/2018, Farmworker Justice conducted the Unidos community mobilization project to raise skin-cancer awareness and promote skin-cancer care access in farmworker communities. Unmet needs were identified in follow-up care coordination for patients who screened positive for a suspicious skin lesion. We undertook this ReUnidos study to document the incidence of skin cancer in the farmworker community and to evaluate the benefits of a health-navigator program to facilitate follow-up care. Methods: Participants (primarily Latinx) are screened in the community setting by volunteer dermatologists. Those who screen positive for suspected skin cancer are invited to participate in the study. They are assigned a trained navigator who addresses the importance of evaluating the lesion, the details of the diagnostic process, and any questions the subjects have. The navigators also help arrange travel, scheduling of appointments, interpretation services, and any other supports needed during the care journey. Data are collected on the number of biopsies performed, diagnoses, time from screening to diagnosis, skin cancer staging, time to treatment, as well as satisfaction with and perceived effectiveness of the navigator program. Outcome measures are extracted from chart review and final semi-structured interviews of both subjects and navigators. The project seeks to screen 1, 000 community members. Approximately 2% are expected to screen positive for a suspicious lesion and require follow-up care. Results: To date, 16 health navigators have been trained and 6 screening events have been conducted in Northern San Diego County by Vista Community Clinic. A total of 126 adult participants have been screened, with 47% identifying as farmworkers. One participant screened positive for a potential skin cancer and has consented to the study. Conclusions: Community-based screenings linked to health-navigation programs may be effective tools to increase access to skin-cancer care among farmworkers. A telemedicine screening model is also being investigated for a second site in upstate New York to expand rural skin screening access. This model may also be useful in care coordination for other malignancies in farmworker communities such as lung cancer and lymphoma, which have also been linked to occupational pesticide exposure.Screening demographics. Screening No. Men Women Farmworker Men Farmworker Women Latinx Rural 1 3 14 3 7 -- -- 2 2 19 2 9 -- -- 3 4 9 3 7 13 10 4 2 13 1 5 13 12 5 2 4 2 0 6 6 6 16 27 10 5 37 10